Ruptured intra-abdominal testicular seminoma with hemorrhage shock, after inadequate surgical exploration for undescended testis: a case report - Hirotake Gonda; Takuya Saito; Takaaki Osawa; Shintaro Kurahashi; Tatsuki Matsumura; Yasuyuki Fukami; Shunichiro Komatsu; Kenitiro Kaneko; Kazuhiro Hiramatsu; Takehito Kato; Tsuyoshi Sano (Surgical Case Reports)
Abstract Background Undescended testes are associated with an increased risk of malignancy and infertility, and surgical treatment in childhood is recommended. Case presentation A 35-year-old man presented to the emergency department with abdominal pain and vomiting. Despite a history of surgery for a left undescended testis in infancy, his left-sided scrotum appeared underdeveloped. Contrast-enhanced computed tomography showed a pelvic mass, involving a major axis of approximately 15 cm, with high-density ascites suggestive of hemorrhage. A ruptured gastrointestinal stromal tumor was suspected. As he was in hemorrhagic shock, an emergency laparotomy was indicated. The active bleeding mass was controlled through complete resection. A pathological evaluation of the mass revealed a seminoma arising from an undescended testis. His post-operative course was uneventful, and he was discharged on post-operative day 6. Recurrence on the retroperitoneal lymph nodes was detected 1 year postoperatively, and a retroperitoneal lymph node dissection was performed after chemotherapy. He remains well without any apparent signs of recurrence. Conclusions Paying close attention to an empty scrotum is advisable, even postoperatively, for undescended testis because of possible subsequent potential malignancy presenting with hemorrhage, as our patient demonstrated.